Construção e avaliação de um programa multimodal de habilidades comunicativas para a adultos com deficiência mental - Aguiar, Adriana Augusto Raimundo de (2006)
Studies in the field of Special Education state that mentally challenged people present difficulties as to communication and interpersonal rapport. This fact has defined the necessity of structuring training programs on these abilities, so that these challenged people can be inserted in the community in an extensive way. Based on these concerns and on the lack of descriptive studies depicting interventions with mentally challenged adults in general and in the field of communicative abilities in particular, the present paper aimed at the following: a) elaboration and description of tools and procedures for the evaluation and promotion of communicative abilities of mentally challenged adults; b) design, implementation and description of a program to promote verbal and non-verbal communicative abilities for a group of mentally challenged adults; c) analyses of each of the program participants performance, according to indicators obtained in different moments of the intervention. Six mentally challenged adults have taken part in this study as well as professional informants and family members. The communicative performance was assessed by means of questionnaires and interviews and direct behavioral observation. The program focused on the training of verbal and non-verbal abilities through mingling techniques associated to pedagogical, cognitive behaviorist and speech- language-hearing approaches. The performances were recorded in scores and organized in protocols, which were subject of individualized analyses as compared to the group, taking under consideration the consistency of changes between the differences before and after the interventions. The results have pointed: positive changes in several trained components, reliable positive changes in some components, as well as in the group participants and family member s satisfaction with the intervention. The contribution of this paper in terms of produced knowledge has been discussed, as well as the performed stages, decisions and challenges of this research-intervention and the importance of investment in researches in this area, involving the construction, adaptation and improvement of social and communicative abilities evaluation tools for the social and communicative abilities for the mentally impaired, in particular the adult population.